LEARNING BASED ON PRINCIPLES OF COGNITIVISM - Khan, Muhammad Junaid; Jamil, Brekhna; Sethi, Ahsan (Journal of Ayub Medical College Abbottabad, 2020)
Sometimes, knowledge or information becomes difficult to understand and/or memorize. Cognitive load theory aids a learner to gain information effectively. It provides a scientific roadmap to the design of learning materials. Through a complex set of mental processes, information is acquiring, process, retain, and comprehend information. Applying mental effort for remembering is a very crucial phenomenon. The core of memory process is apprehending and saving of information into long term memory. Because of limited capacity of working memory, delivering or acquiring of information should not be overloaded with irrelevant materials. Based on cognitive load theory dozens of strategies can be intervened at different loci of cognitive process and every piece of information is easily remembered. Not only learners, but teachers can also get benefits from them. In this commentary, John Sweller ideology is further discussed and strategies are presented for better comprehension and memorization of difficult information. Keywords: memorize, memory process; learning; cognitive load theory